Evolution in Board Chair–CEO Relationships: A Negotiated Order Perspective. (October 2016) - Cornforth, Chris; Macmillan, Rob
The relationship between chairs and chief executive officers (CEOs) has been largely neglected in research on nonprofit governance. Yet, a growing body of research on corporate governance in the private and public sectors suggests that this relationship is crucial both to the effective functioning of the board and the leadership of the organization. Much of the research on chair–CEO relationships has used cross-sectional research designs ignoring the fact that these relationships will evolve over time. This article responds to some of these challenges. It presents the results from longitudinal research examining the relationship between the chair and chief executive in a nonprofit organization. It shows how this relationship is "negotiated" and develops over time in response to contextual changes.